EFFECT OF ADDING RECYCLED PLASTIC FIBERS TO CONCRETE ON THE STATIC PROPERTIES OF CONCRETE TILES - Hussain, Ahmed Hammad; Ahmed, Ahmed Mohmmed; Hammood, Mohammed Taha; Abdulla, Aziz (Anbar Journal of Engineering Sciences, 2020)
This research paper is an attempt to reuse plastic waste fibre resulting from plastic sections industry as an additive to concrete matrix. The relationship between fibre volume fraction and mechanical properties of concrete and re-inforced concrete tiles was investigated. Three volume fractions of fibre ( 0.5 % , 1 % and 1.5 % - by volume of concrete ) were used through the experi-mental program. Tests’ results proved a slight decrease in concrete compres-sive strength as plastic fibre was added compared with the reference mix. Flexural behaviour of concrete tiles was enhanced as adding fibres. Adding fibre to Concrete results in a negligible reduction in concrete density. Fibre with high volume fractions improved Splitting tensile strength compared to the reference mix.